(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Management of threatened abortion is very important among the pregnant women. Objective: The purpose of the present study was to assess the clinical profiles, conservative management and outcomes of threatened abortion. Methodology: This cross-sectional study was done in the Department of Obstetrics & Gynaecology at Rajshahi Medical College Hospital, Dhaka, Bangladesh from January 2004 to December 2004 for a period of one year. Patients admitted with the history of pregnancy with per vaginal bleeding before 20 weeks without having any cervical effacement or dilatation were included in this study group. The clinical profiles, conservative management and outcomes of threatened abortion cases were recorded from the study population. Results: The threatened abortion was reported at all stage of reproductive age. Women between 20 to 30 years had constituted the largest age group (58.0%). Most of the patients (82 among the 100) were multi gravidas with only 18 who were pregnant for the first time. Most of the patients (48.0%) are of 8 to 12 weeks of gestation. However, 12 to 16 weeks period f gestation was reported in 48.0% cases. Less than 30% of hemoglobin was reported in 20.0% cases. However, 30.0% to 40.0% hemoglobin was recorded in 16.0% cases. Furthermore, 40.0% to 50.0% hemoglobin was reported in 60.0% cases. Urinary tract infection was reported in 7.0% cases. Conclusion: In conclusion threatened abortion is most commonly reported in early gestation og age with low hemoglobin with bad obstetrical outcomes. Bangladesh Journal of Medical Microbiology, July 2024;18(2):80-85